2008
DOI: 10.1590/s0100-29452008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Atividade da pectinametilesterase e sua relação com a perda de firmeza da polpa de mamão cv. Sunrise Solo e Tainung

Abstract: O objetivo deste trabalho foi avaliar a atividade da pectinametilesterase (PME) em mamão (Carica papaya L.), cv. Sunrise Solo e Tainung, e relacionar suas alterações com a perda de firmeza da polpa durante o amadurecimento. Os frutos foram coletados diariamente em uma lavoura comercial em Aracruz - ES, e armazenados sob temperatura ambiente (aproximadamente, 25ºC) até o período das análises. A perda da firmeza da polpa dos frutos das cultivares iniciou-se no 4º dia após a colheita (DAC); entretanto, a cv. Sunr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
4
0
9
Order By: Relevance
“…Pinto et al (2011) found high Pme activity at the beginning of storage of 'golden' papaya, which decreased sharply until the third day, coinciding with the early fruit ripening. Similar results were found by Fontes et al (2008), in which the Pme activity of 'Sunrise Solo' papaya was high on the first day after harvest and reduced gradually until the 4 th day, when it reached its lowest value.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Pinto et al (2011) found high Pme activity at the beginning of storage of 'golden' papaya, which decreased sharply until the third day, coinciding with the early fruit ripening. Similar results were found by Fontes et al (2008), in which the Pme activity of 'Sunrise Solo' papaya was high on the first day after harvest and reduced gradually until the 4 th day, when it reached its lowest value.…”
Section: Resultssupporting
confidence: 86%
“…this marked reduction in firmness observed in all treatments is due to fruit ripening. Differences were significant only in the first day of evaluation (table 1), and damage by abrasion resulted in lower firmness, which was also observed by Godoy et al (2010). This lower firmness may be related to greater weight loss caused by this damage, because according to Kays (1991), fresh weight loss results in less hydration of cells and hence lower pulp firmness.…”
Section: Resultsmentioning
confidence: 84%
“…The pulp firmness was determined by means of pulp penetration resistance measurements according to Fontes et al (2008). Initially, each fruit was longitudinally sectioned in two faces.…”
Section: Methodsmentioning
confidence: 99%
“…Ali et al (2004) constataram que o início da perda de firmeza dos frutos de carambola, goiaba, banana e mamão foi acompanhada pelo aumento da atividade da PME. Fontes et al (2008), avaliaram a relação entre a firmeza e a atividade da PME da polpa de mamão cv. Sunrise Solo, e constataram que à medida que a firmeza da polpa decresceu, a atividade da PME aumentou.…”
Section: Fonte: Elaboração Dos Autoresunclassified